2017
DOI: 10.4103/0366-6999.202735
|View full text |Cite
|
Sign up to set email alerts
|

Biliverdin Protects the Isolated Rat Lungs from Ischemia-reperfusion Injury via Antioxidative, Anti-inflammatory and Anti-apoptotic Effects

Abstract: Background:Biliverdin (BV) has a protective role against ischemia-reperfusion injury (IRI). However, the protective role and potential mechanisms of BV on lung IRI (LIRI) remain to be elucidated. Thus, we aimed to investigate the protective role and potential mechanisms of BV on LIRI.Methods:Lungs were isolated from Sprague-Dawley rats to establish an ex vivo LIRI model. After an initial 15 min stabilization period, the isolated lungs were subjected to ischemia for 60 min, followed by 90 min of reperfusion wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Here, we found that IR significantly induced both apoptotic and necrotic cell death in the lung tissue. Caspase-dependent apoptosis is considered as a classical contributor to IR-induced lung injury, and the effectiveness of antiapoptotic therapies has been well demonstrated in previous studies [ 5 , 6 , 20 , 21 ]. In this study, z-VAD-fmk, a pan caspase inhibitor, significantly reduced apoptotic cell death and pathological severity in the lung tissue and decreased inflammatory markers and protein levels in BAL fluid as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we found that IR significantly induced both apoptotic and necrotic cell death in the lung tissue. Caspase-dependent apoptosis is considered as a classical contributor to IR-induced lung injury, and the effectiveness of antiapoptotic therapies has been well demonstrated in previous studies [ 5 , 6 , 20 , 21 ]. In this study, z-VAD-fmk, a pan caspase inhibitor, significantly reduced apoptotic cell death and pathological severity in the lung tissue and decreased inflammatory markers and protein levels in BAL fluid as well.…”
Section: Discussionmentioning
confidence: 99%
“…Necroptosis shares similar morphologic features with necrosis, and accumulating evidences have highlighted its importance in mediating various pathophysiologic events [ 12 , 24 29 ]. Mixed lineage kinase domain-like protein (MLKL) is identified as a key component downstream of RIP3 in the execution of RIP1-mediated necroptosis, and MLKL trimerization and translocation facilitate the channel formation on the plasma membrane through which DAMPs are released [ 21 , 30 , 31 ]. Thus, necroptosis is typically characterized by cellular swelling and rupture, and the loss of cellular membrane integrity would promote inflammation via the release of DAMPs into the extracellular environment [ 22 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A variety of studies have shown that, in the development and manifestations of ALI, apoptosis is thought to be closely related to the severity of ALI [58,59]. For example, extensive apoptosis of pulmonary alveolar type II epithelial cells has been shown to be responsible for the impairment of the epithelial barrier function and the remodeling of certain mesenchymal cells in ALI [60].…”
Section: Discussionmentioning
confidence: 99%
“…Haptoglobin may also interface with other anti-inflammatory pathways, as it stimulates the expression of heme oxygenase (Belcher et al, 2018), the enzyme responsible for converting heme from its pro-oxidant form to a molecule called biliverdin (Medzhitov et al, 2012;McDonagh, 2001). Biliverdin has anti-inflammatory (Tian et al, 2017) and anti-viral (Zhu et al, 2010) properties, and also has putative antioxidant properties (Baylor and Butler, 2019;Mancuso et al, 2012). Thus, inflammation may simultaneously result in an increase in oxidative damage, while also promoting the production of molecules and enzymes associated with anti-inflammatory and antioxidant functions.…”
Section: Introductionmentioning
confidence: 99%